Role of Oocyte Morphological Abnormality Rates on the Embryo Development and Implantation - Bilgic, Bulent Emre; Yayla Abide, Cigdem; Ozkaya, Enis; Kutlu, Tayfun; Ayla, Sule; Sanverdi, Ilhan; Tunali, Gulden; Yucel, Erdal; Kanbur, Savas (Gynecology Obstetrics & Reproductive Medicine, 2018)
OBJECTIVE: The aim of this study was to assess the impact of some oocyte morphological abnormality rates on embryo development and implantation. STUDY DESIGN: Oocyte morphological abnormalities including oocyte size, elliptical shape, vacuole, plain polar body, fragmented polar body, large perivitellin space, perivitellin debris, central granulation, dense central granulation, inclusion body, thick zona pellucida, clusters of smooth endoplasmic reticulum, easy needle insertion and dark cytoplasm were determined for each oocyte. Rates of these oocyte morphological anomalies were determined for each case and the impact of rates on the cycle outcome was analyzed. RESULTS: Similar oocyte morphology abnormality rates were observed between cycles with and without successful embryo implantation. On the other hand, both fragmented polar body and vacuole rates were found to be significantly higher in cycles with Grade 2 embryo transfer. These rate differences were remained significant after adjustment for the age and basal FSH level. CONCLUSION: None of the oocyte morphological features was found to have significant impact on ART outcome.